(untitled) (مجلة المنصور, 2023)
The Genetic Algorithms can be considered as modern active way for finding optimum solution for many engineering problems as where as electronics , power , communication engineering. This optimum location has been detected with a low number of iteration . this optimazation can be used for many civilian application such as location of electrical power station , location of communication center or other to reduce the price/ km for transmission line . this optimization problem have been run with a special genetic algorithm called ( Gas play ground ) with suitable genetic input file.